Effect of Sample Storage on Stability of Salivary Glutathione, Lipid Peroxidation Levels, and Tissue Factor Activity - YARAT, AYŞEN; ALTURFAN, EBRU IŞIK (WILEY, 2009)
Saliva samples are often required to be stored for longer periods of time either because of the project protocol or because of lack of funding for analysis. The effects of 6 months storage (fresh, 30, 60, 90 120, 150, and 180d) on the stability of salivary reduced glutathione (GSH), lipid peroxidation (LPO) and 90days of storage (fresh, 15, 30, 60, and 90d) on the stability of salivary tissue factor (TF) activity and the stability of saliva imprint samples at 20 C were evaluated in this study. Salivary GSH, malondialdehyde (MDA) levels as an index of LPO, and TF activities were determined using the methods of Beutler, Yagi, and Quick, respectively. Saliva imprint samples were stained with Giemsa and microscopically examined. Salivary GSH levels and TF MDA levels increased significantly after 6 months of storage at -20 C. Leucocyte, epithelium and bacterium cell counts did not significantly change at the end of 90 d of storage. Saliva samples may be stored up to 1 month at -20 C for LPO assay. For cytological examinations, saliva samples may be stored for 90 d at -20 C. Further studies are needed to determine the stability of salivary GSH, and salivary TF activity stored less than 30 days at -20 C. On the other hand, if saliva samples are required to be stored, to avoid the changes because of different storage periods, we recommend that they must be stored under the same circumstances and in the same time period. J. Clin. Lab. Anal. 23:93-98, 2009. (C) 2009 Wiley-Liss, Inc.
Keywords: saliva; storage; tissue factor; glutathione; lipid peroxidation; HUMAN-BLOOD; TOXICITY; PLASMA; CELLS; SERUM; PARAMETERS; RESISTANCE; DISEASE